Football on TV: an empirical analysis on the italian "couch" potato attitudes - Di Domizio, Marco (Papeles de Europa, 2013)
This paper investigates the relationship between Football and TV audience looking for empirical evidences from Italian Serie A. The analysis traces previous econometric study, based on season 2008/09, focusing on season 2009/10. Data on 380 matches played in the Italian top professional football league are collected in order to select variables suitable of influencing the share of TV audience on satellite television. We try to estimate the «Football on TV» demand by an OLS regression model introducing a set of independent variables about the match quality, the TV programming placement, the market size of teams and their rank. In addition, our attention concentrates on the relationship between the closeness of the game and the television audience, where uncertainty of outcome is modelled using information from the betting market. It emerges that many of the theoretical expected relationships are confirmed by the econometric analysis, even though some peculiarities emerge with respect to the uncertainty of outcome issue. In particular, closer contexts are important in determining the interest of sporting events, also from the Italian TV audience perspective, but they are not crucial. If the set of explanatory variables includes both the uncertainty of outcome and teams probabilities of winning, a negative relationship between the closeness of the match and TV audience emerges. This result suggests two possible explanations. First, the TV spectators behave just like stadium fans, and they are mainly interested in their own team victory. Second, the negative relationship may be attributed to the «David versus Goliath» hypothesis since neutral positioned fans watch matches on TV in the hope that little teams defeat top ranked teams. Finally, our empirical analysis confirms the decisive role of Inter, Juventus and Milan in determining the size of couch potato audience, supporting the idea of big teams’ management that the competitive balance has not a great commercial appeal, and that the collective bargaining of TV rights must not be justified on this ground.